2018
DOI: 10.31739/ggzv.2018.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Hersenactiviteit tijdens een paniekaanval

Abstract: Correspondentieadres:andres@adagioamsterdam.nl SamenvattingDe heer V. (V.) lijdt sinds zijn jeugd onder een specifieke fobie met paniekstoornis. De paniek start wanneer hij de grenzen van zijn woonplaats bereikt, onafhankelijk van het type vervoer waarmee hij reist. Ook speelt de bestemming geen rol in het ontstaan of de ernst van de paniekaanval. Tijdens een autorit die een paniekaanval uitlokte zijn EEG opnames gemaakt. bèta activiteit (van 13-30 Hz.) bleek over grote delen van de cortex toe te nemen tijdens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The results of the meta-analysis on these studies confirmed the efficacy of BBs in the reduction of anxiety scores after delta/theta exposure. Other studies, which focused primarily on brain activity during high levels of anxiety, mention relatively reduced theta activity and relatively increased beta activity (Engelbregt, Keeser, Promes, Verhagen-Schouten, & Deijen, 2012;Guevara et al, 2018;Kara & Polo, 2014;Schicho & Pogarell, 2014). It is therefore important that while studying BB, researchers pay attention to possible side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the meta-analysis on these studies confirmed the efficacy of BBs in the reduction of anxiety scores after delta/theta exposure. Other studies, which focused primarily on brain activity during high levels of anxiety, mention relatively reduced theta activity and relatively increased beta activity (Engelbregt, Keeser, Promes, Verhagen-Schouten, & Deijen, 2012;Guevara et al, 2018;Kara & Polo, 2014;Schicho & Pogarell, 2014). It is therefore important that while studying BB, researchers pay attention to possible side effects.…”
Section: Introductionmentioning
confidence: 99%